2010
DOI: 10.1088/2041-8205/721/2/l172
|View full text |Cite
|
Sign up to set email alerts
|

On the Puzzle of Space Weathering Alteration of Basaltic Asteroids

Abstract: The majority of basaltic asteroids are found in the inner main belt, although a few have also been observed in the outer main belt and near-Earth space. These asteroids-referred to as V-types-have surface compositions that resemble that of the 530 km sized asteroid Vesta. Besides the compositional similarity, dynamical evidence also links many V-type asteroids to Vesta. Moreover, Vesta is one of the few asteroids to have been identified as source of specific classes of meteorites, the howardite, eucrite, and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…The strength of the bands observed for the Vestoids are much closer to that observed in laboratory studies of meteorites (Binzel and Xu 1993;Hiroi et al 1995;Pieters et al 2006). Marchi et al (2010), Moskovitz et al (2010), andDe Sanctis et al (2011b) investigated several of the small Vestoids using earth-based telescopes and found that their visible slopes are generally redder than that of Vesta and systematically redder than HEDs measured in the laboratory. The observed trend for Vestoids (steeper continuum, stronger absorption bands) is opposite that observed for S-type asteroids (steeper continuum, weaker absorption bands), again suggesting that Vesta and its family of small asteroids is distinctive.…”
Section: Spwe: Dawn Science Objectivessupporting
confidence: 76%
See 1 more Smart Citation
“…The strength of the bands observed for the Vestoids are much closer to that observed in laboratory studies of meteorites (Binzel and Xu 1993;Hiroi et al 1995;Pieters et al 2006). Marchi et al (2010), Moskovitz et al (2010), andDe Sanctis et al (2011b) investigated several of the small Vestoids using earth-based telescopes and found that their visible slopes are generally redder than that of Vesta and systematically redder than HEDs measured in the laboratory. The observed trend for Vestoids (steeper continuum, stronger absorption bands) is opposite that observed for S-type asteroids (steeper continuum, weaker absorption bands), again suggesting that Vesta and its family of small asteroids is distinctive.…”
Section: Spwe: Dawn Science Objectivessupporting
confidence: 76%
“…Since the discovery that Vesta's near-infrared reflectance spectrum is closely comparable to laboratory measurements of particulate samples of unweathered HED meteorites (McCord et al 1970), it has been believed that Vesta's surface shows little or no evidence of space weathering alteration. On the other hand, laboratory experiments conducted on HEDs, and pyroxene constituents, suggest that Vesta-like materials should indeed alter under the effects of ion bombardment and micrometeorite impacts in a way similar to that observed for ordinary chondrite-like materials, but at Vesta the alteration timescale is longer (Hiroi and Pieters 1998;Marchi et al 2005;Vernazza et al 2006). The many controlling variables on the rate of changes with space weathering are poorly constrained.…”
Section: Spwe: Dawn Science Objectivesmentioning
confidence: 99%
“…Most of them are nonfamily members, according to the Nesvorn媒 et al (2008) definition. The mean orbital parameters, taken from the astdys web site (http://hamilton.dm.unipi.it/astdys/), the absolute magnitude and the diameter, obtained assuming an albedo of 0.3 as in Marchi et al (2010), are provided in Table 1.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The asteroid spectra were finally normalized to achieve a reflectance value equal to 1 around 1.6 渭m. Marchi et al (2010). The family membership has been defined as in Nesvorn媒 et al (2008).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation